2017
DOI: 10.1007/s10753-017-0541-5
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin and Simvastatin Promoted Mouse Lung Repair After Cigarette Smoke-Induced Emphysema

Abstract: Cigarette smoke (CS) induces pulmonary emphysema by inflammation, oxidative stress, and metalloproteinase (MMP) activation. Pharmacological research studies have not focused on tissue repair after the establishment of emphysema but have instead focused on inflammatory stimulation. The aim of our study was to analyze the effects of atorvastatin and simvastatin on mouse lung repair after emphysema caused by CS. Male mice (C57BL/6, n = 45) were divided into the following groups: control (sham-exposed), CSr (mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Melo et al [ 21 ] evaluated the effects of ATR, pravastatin, and simvastatin on endotoxin-induced ALI and showed that ATR and pravastatin but not simvastatin revealed anti-inflammatory activity. Pinho-Ribeiro et al [ 51 ] evaluated the effects of ATR and simvastatin on mouse lung emphysema induced by cigarette smoke. The result indicated that ATR showed a better anti-inflammatory activity compared with simvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Melo et al [ 21 ] evaluated the effects of ATR, pravastatin, and simvastatin on endotoxin-induced ALI and showed that ATR and pravastatin but not simvastatin revealed anti-inflammatory activity. Pinho-Ribeiro et al [ 51 ] evaluated the effects of ATR and simvastatin on mouse lung emphysema induced by cigarette smoke. The result indicated that ATR showed a better anti-inflammatory activity compared with simvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…The repurposing of statins, as an inhaled therapy, is one such strategy as it delivers higher concentrations of drug to the lungs at lower drug dosages as compared to oral delivery 62, 63. There are increasing lines of evidence showing the potential and benefits of using inhaled statins in mouse models with inflammatory lung diseases 64-66. Further investigations are needed to translate the inhaled formulation to the clinical setting for the treatment of NSCLC with EGFR-TKI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The statins inhibit the influx of inflammatory cells into airway and lung tissues (e.g. neutrophils, eosinophils, lymphocytes, macrophages) [31,36,138], and reduce airway smooth muscle cell proliferation [43], oxidative stress [129], fibrosis [44], cytokine production [34,139], and mucus production [140]. The statins also induce apoptosis in cancerous or proliferative cells and airway mesenchymal cells [141], enhance macrophage efferocytosis [142], increase endothelial cell nitric oxide production [37], and improve cell barrier integrity [143].…”
Section: Figurementioning
confidence: 99%